2013
DOI: 10.7840/kics.2013.38b.8.607
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Power Law: A View from VoD Service

Abstract: In this work we investigate the power of power law in the VoD service over IP network. Especially, we show that the power of power law is strong in the location of the contents storage for the VoD service and its impact on the link dimensioning. This work first shows the instance of the power law in the popularity of the video contents from the real data for the IPTV service. After that we propose an analytic model that characterizes the behavior of customers in accessing the video servers as well as the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Recently, it is reported that the location of cache near the customers saves the operation cost as well as the traffic of the network as compared with a single point of storage at CP [15] . Note also that the location of contents has a vital impact on the benefit of multicast.…”
Section: Benefit Of Multicastmentioning
confidence: 99%
“…Recently, it is reported that the location of cache near the customers saves the operation cost as well as the traffic of the network as compared with a single point of storage at CP [15] . Note also that the location of contents has a vital impact on the benefit of multicast.…”
Section: Benefit Of Multicastmentioning
confidence: 99%
“…They introduced small-world network model, which is highly clustered like regular lattice, yet has small average shortest path length like random network. It is known small-world network characterizes many real world networks such as the social network [7] , the biochemical network [8] , the Internet [2,9] , VoD service over IP network [10] , and etc. The other finding is scale-free network.…”
Section: ⅰ Introductionmentioning
confidence: 99%